Knowledge and attitude of dentists in care of persons with desability - Córdoba, Doris; España, Sorany del Socorro; Tapia, Genny Liliana (Universidad y Salud, 2012)
The objective of this article is to carry out a state of the art review of the attitude and knowledge of dentists regarding the attention of people with intelectual disability. Scientific literature is coincidental in showing that intellectually disabled people exhibit high prevalence in tooth decay, periodontal disease, loss of teeth, bad oral hygiene and sometimes they do not have the familiar support or minders to improve the conditions of oral health and to implement preventive treatments and of reabilitation. This population group is considered to be vulnerable and in need of integal dental attention. The research was done using the MEDLINE, Redalyc, Scielo databases on studies related to this subject. In conclusion, the studies reveal that in the dental attention of patients with intellectual disability, there is a lack of knowledge and/or training of the professionals, additionally; negative attitude appears more frequently in middle age dentist. Nevertheless, the more work experience the dentist has, the more effectiveness there is in the treatment implementation.